1967
DOI: 10.1113/jphysiol.1967.sp008260
|View full text |Cite
|
Sign up to set email alerts
|

Cortical responses to paired stimuli applied peripherally and at sites along the somato‐sensory pathway

Abstract: SUMMARY1. Experiments have been performed on animals anaesthetized with various anaesthetics to determine the responsiveness of the cortex to the second of a pair of identical stimuli applied at three sites along the sensory pathway, i.e. to the periphery, the medial lemniscus and to thalamocortical fibres.2. It has been found that in deeply anaesthetized animals the mass response recorded from the cerebral cortex to the second of a pair of peripheral or lemniscal stimuli became reduced in size if the interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…With regard to 7 day old S I topographical arrangement, the relative positions of somatotopically organized columns compares favourably with the projection found in the adult (Woolsey & Le Messurier, 1948;Angel, 1967;Carter, Holmes & Houchin, 1969;Welker, 1971). Furthermore the relative amount of cortex devoted to handling information from particular areas of skin appears to be similar at the two ages.…”
Section: Discussionsupporting
confidence: 54%
“…With regard to 7 day old S I topographical arrangement, the relative positions of somatotopically organized columns compares favourably with the projection found in the adult (Woolsey & Le Messurier, 1948;Angel, 1967;Carter, Holmes & Houchin, 1969;Welker, 1971). Furthermore the relative amount of cortex devoted to handling information from particular areas of skin appears to be similar at the two ages.…”
Section: Discussionsupporting
confidence: 54%
“…Several subsequent studies have shown that one effect of this is a diminution in the responsiveness of cortical cells following a punctate cutaneous stimulus, displacement of a single facial vibrissa, and/or electrical shock to a peripheral nerve (2,12,18,43). This decreased responsiveness is seen as a reduction in the number of unit discharges elicited by the second of two equally intense stimuli and is most pronounced during the lo-20 ms after the first stimulus.…”
Section: Temporal Integrationmentioning
confidence: 99%
“…Inhibition of the somatosensory system follows excitation, which can be shown in physiological studies with somatosensory‐evoked potential (SEP) technique using a peripheral paired‐pulse paradigm. In both normal animals and humans, a conditioning (preceding) stimulus induces suppression of SEP amplitudes evoked by a following test stimulus 7–9. This inhibitory action is believed to be important in preserving the temporal separation of serially administered stimuli and in enhancing the contrast among them.…”
mentioning
confidence: 99%